Some demographic aspects of Chinese population in Malaysia - Wan Ahmad, Wan Ibrahim (International digital organization for scientific information (IDOSI), 2014)
The Chinese population is an important demographic component in Malaysia.Starting with a mass inmigration of Chinese population from China at the end of the 19 century, Malaysia is now regarded as a multy-ethnic society.The establishment of British rule in Penang, Melaka and Singapore at the turn of the twentieth century marks the beginning of mass Chinese settlement in Malaysia.Using secondary data taken from the Report of Population and Housing Census of Malaysia and various books on Chinese community, it reveals that today this population makes up more than half of the Malay itself.The Chinese population focused on specific states that have a higher level of urbanization.This is in line with business activities that form the backbone of this population since the beginning of their mass inmigration from China. For the states of Perlis, Kedah, Kelantan, Terengganu and Pahang where padi cultivation is dominant, the Chinese is not significant.